Effect of the pre-taper level of fatigue on the taper-induced changes in performance in elite swimmers - Quentin Bretonneau; Antonio Morales-Artacho; Robin Pla; Laurent Bosquet (Frontiers Media S.A., 2024)
IntroductionIn swimming, performance gains after tapering could be influenced by the pre-taper level of fatigue. Moreover, this level of fatigue could be associated with sleep. This study aimed to assess (1) the effect of tapering on performance according to the pre-taper level of fatigue in swimmers and (2) the association between sleep and pre-taper level of fatigue.MethodsPhysiological, psychological and biomechanical profiles were evaluated in 26 elite swimmers on 2 occasions to estimate the pre-taper level of fatigue: at T0 and T1, scheduled respectively 10 and 3 weeks before the main competition. Sleep quantity and quality were also evaluated at T0 and T1. Race time was officially assessed at T0, T1 and during the main competition. The level of significance was set at p ≤ .05.ResultsFourteen swimmers (17 ± 2 years) were allocated to acute fatigue group (AF) and 12 swimmers (18 ± 2 years) to functional overreaching group (F-OR). From T1 to the main competition, performance was improved in AF (+1.80 ± 1.36%), while it was impaired in F-OR (−0.49 ± 1.58%, p < 0.05 vs. AF). Before taper period, total sleep time was lower in F-OR, as compared to AF. Conversely, the fragmentation index was higher in F-OR (p = .06). From wakefulness to sleep, body core temperature decreased in AF but not in F-OR.DiscussionPerformance gain after tapering was higher in AF swimmers than in overreached. Moreover, pre-taper sleep was poorer in overreached swimmers, which could contribute to their different response to the same training load. This poorer sleep could be linked to a lower regulation of internal temperature.